1997
DOI: 10.1021/bi961465y
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Efficient Substrates in Enhancement of Peroxidase-Catalyzed Oxidations

Abstract: Efficient peroxidase substrates may have a critical role in the oxidation of secondary compounds by peroxidases. Hydrazines are often oxidized slowly by peroxidases due, in part, to hydrazine-dependent inactivation of these enzymes. Peroxidase-catalyzed oxidation of hydrazines may be dramatically affected by an efficient peroxidase substrate. We investigated this hypothesis in a model system using the well-known peroxidase substrate chlorpromazine (CPZ) and the hydrazine derivative isoniazid. CPZ stimulated is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
46
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 31 publications
9
46
0
1
Order By: Relevance
“…It has been reported that the catalytic efficiency for oxidation of some peroxidase substrates can be enhanced by the presence of a secondary substance (co-oxidation). 18,19) In confirmation of this, here we verified that the rate of rifampicin oxidation increased in a concentration-dependent manner when TMB was added to the reaction mixture (Fig. 3A).…”
supporting
confidence: 75%
See 1 more Smart Citation
“…It has been reported that the catalytic efficiency for oxidation of some peroxidase substrates can be enhanced by the presence of a secondary substance (co-oxidation). 18,19) In confirmation of this, here we verified that the rate of rifampicin oxidation increased in a concentration-dependent manner when TMB was added to the reaction mixture (Fig. 3A).…”
supporting
confidence: 75%
“…For instance, hydroquinone was described as an effective activator of ascorbic acid oxidation, and chlorpromazine was found to promote the oxidation of isoniazid, in both cases by HRP-catalyzed reactions. 18,19) In such cases, the better substrate is oxidized first by the oxidized intermediate forms of peroxidases and its product is the oxidizing agent for the second substrate. This suggests that the extreme differences observed in our results between the anti-inflammatories might be related to their reactivity with HRP.…”
Section: Discussionmentioning
confidence: 99%
“…These reactions might account for the increase in K i for H 2 O 2 due to the hydrazides. Goodwin et al [11] reported that ISD enhanced the H 2 O 2 -dependent inactivation of horseradish peroxidase. The report suggested that inactivation rate enhancement by ISD may involve a mechanism similar to that due to H 2 O 2 alone.…”
Section: Hydrazides Enhancement Of H 2 O 2 -Dependent Inactivation Ofmentioning
confidence: 99%
“…In this study, we have used a steady state kinetics approach to demonstrate that MPO is irreversibly inactivated by excess H 2 O 2 in the absence of reducing substrate. The rate of the inactivation process is enhanced in the presence of suicide substrates, isoniazid (ISD) and hydralazine (HDL), which are known inactivators of the enzyme [10,11]. We also describe a novel bimolecular rate constant that formally describes the activating effect of a suicide donor substrate on hydroperoxideinitiated inactivation of peroxidases.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the presence of excess H 2 O 2 relative to HRP, it is well known that other forms, such as compound III and P-670, are formed in addition to compounds I and II. [27][28][29][30] These results indicate that the concentration of H 2 O 2 in reaction solutions affect the fluorescent derivatization of QA with HRP.…”
Section: Effects Of Concentration Of H 2 O 2 and Hrpmentioning
confidence: 81%